Materials Procurement Management in the Construction Sector (the Challenge of Project Managers) - Moreno-Ramírez, Brenda D. C. (EFIM Ediciones, 2022)
Nowadays, an adequate project management starts from a good procurement management which is necessary for the achievement of the project goals, and even for the development of the processes in the organizations, starting from a chain of requirements that must be carried out to ensure the achievement of the expected results in terms of cost, time and quality. Objective: to investigate in depth and make known the development of a good procurement management specifically applied in a company of the construction projects sector according to the guidelines of different authors who applied this concept in different sectors. Method: literature review of different authors, pmbok guide and scientific magazines as well as the bibliographic review of other articles, thesis, books and degree works on procurement management in organizations. Conclusions: the problem of procurement management in Latin America affecting the successful achievement of different projects was evidenced, information from different authors, countries and approaches that show different tools and techniques that provide great value to this topic in companies was reviewed.